2017
DOI: 10.1007/978-3-319-61615-5_4
|View full text |Cite
|
Sign up to set email alerts
|

Sources and Fate of Microplastics in Urban Areas: A Focus on Paris Megacity

Abstract: Since the beginning of the 2010s, the number of investigations on microplastics in freshwater increased dramatically. However, almost no study aims at investigating the various sources and fate of microplastics in a catchment. This chapter aims at analyzing the various sources and fate of microplastics for an urban catchment and its hydrosystem (sewage, runoff, etc.). It presents the results obtained during a 3-year study of the Paris Megacity. Such a study required the development of appropriate sampling stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
98
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(107 citation statements)
references
References 20 publications
6
98
3
Order By: Relevance
“…MPs have several potential environmental release pathways: (1) passage through WWTPs, either from MP use in personal care products or release of fibres from textiles during the washing of clothes, to surface waters, (2) application of biosolids from WWTPs to agricultural lands [50], (3) storm water overflow events, (4) incidental release (e.g. during tyre wear), (5) release from industrial products or processes, and (6) atmospheric deposition of fibres (discussed further in Dris et al [51]). Plastic films used for crop production are considered an important agricultural emission, and their use is thought to be one of the most important sources of plastic contamination of agricultural soils [52][53][54].…”
Section: Sources Of Plastics and Microplastics Into The Freshwater Enmentioning
confidence: 99%
See 1 more Smart Citation
“…MPs have several potential environmental release pathways: (1) passage through WWTPs, either from MP use in personal care products or release of fibres from textiles during the washing of clothes, to surface waters, (2) application of biosolids from WWTPs to agricultural lands [50], (3) storm water overflow events, (4) incidental release (e.g. during tyre wear), (5) release from industrial products or processes, and (6) atmospheric deposition of fibres (discussed further in Dris et al [51]). Plastic films used for crop production are considered an important agricultural emission, and their use is thought to be one of the most important sources of plastic contamination of agricultural soils [52][53][54].…”
Section: Sources Of Plastics and Microplastics Into The Freshwater Enmentioning
confidence: 99%
“…Reddy et al [59]) and may exclude those in the submicron size ranges. The environmental occurrence and sources of MPs in freshwater matrices in an African, Asian, and European context are further discussed in Dris et al [51], Wu et al [60], Khan et al [61], respectively.…”
Section: Occurrence In Freshwater Systemsmentioning
confidence: 99%
“…The first notion of seabirds ingesting plastic debris was published in the 1960s [12]. At this point, research into environmental contamination with plastic debris was a small field, and few papers were published through the 1960s and 1970s (see [13][14][15]). However, Carpenter and Smith [16] were the first to notice that plastic accumulated in specific oceanic zone, in their Science publication of plastic debris in the Sargasso Sea.…”
Section: Historical Developmentmentioning
confidence: 99%
“…So far, only one study reports significant impacts of MP on fish larvae at concentrations found in coastal waters [51]. 4 Nevertheless, MPs occur in almost all types of freshwater environmentsranging from streams in densely populated areas to lakes in almost non-populated areas, e.g., in Mongolia ( [52][53][54][55], [19,56,57]; see [58,59] for further discussion). Additionally, MPs persist over centuries under common environmental conditions [60].…”
Section: Do We Need Regulation Of Microplastics At All?mentioning
confidence: 99%